Identification of the Hepatic Metabolites of Flumazenil and their Kinetic Application in Neuroimaging - Wei-Hsi Chen; Chuang-Hsin Chiu; Shiou-Shiow Farn; Kai-Hung Cheng; Yuan-Ruei Huang; Shih-Ying Lee; Yao-Ching Fang; Yu-Hua Lin; Kang-Wei Chang (MDPI AG, 2023)
Studies of the neurobiological causes of anxiety disorders have suggested that the γ-aminobutyric acid (GABA) system increases synaptic concentrations and enhances the affinity of GABAA (type A) receptors for benzodiazepine ligands. Flumazenil antagonizes the benzodiazepine-binding site of the GABA/benzodiazepine receptor (BZR) complex in the central nervous system (CNS). The investigation of flumazenil metabolites using liquid chromatography (LC)-tandem mass spectrometry will provide a complete understanding of the in vivo metabolism of flumazenil and accelerate radiopharmaceutical inspection and registration. The main goal of this study was to investigate the use of reversed-phase high performance liquid chromatography (PR-HPLC), coupled with electrospray ionization triple-quadrupole tandem mass spectrometry (ESI-QqQ MS), to identify flumazenil and its metabolites in the hepatic matrix. Carrier-free nucleophilic fluorination with an automatic synthesizer for [18F]flumazenil, combined with nano-positron emission tomography (NanoPET)/computed tomography (CT) imaging, was used to predict the biodistribution in normal rats. The study showed that 50% of the flumazenil was biotransformed by the rat liver homogenate in 60 min, whereas one metabolite (M1) was a methyl transesterification product of flumazenil. In the rat liver microsomal system, two metabolites were identified (M2 and M3), as their carboxylic acid and hydroxylated ethyl ester forms between 10 and 120 min, respectively. A total of 10-30 min post-injection of [18F]flumazenil showed an immediate decreased in the distribution ratio observed in the plasma. Nevertheless, a higher ratio of the complete [18F]flumazenil compound could be used for subsequent animal studies. [18F] According to in vivo nanoPET/CT imaging and ex vivo biodistribution assays, flumazenil also showed significant effects on GABAA receptor availability in the amygdala, prefrontal cortex, cortex, and hippocampus in the rat brain, indicating the formation of metabolites. We reported the completion of the biotransformation of flumazenil by the hepatic system, as well as [18F]flumazenil's potential as an ideal ligand and PET agent for the determination of the GABAA/BZR complex for multiplex neurological syndromes at the clinical stage.